Ibnu Qayyim Al-Jauziyyah's Ways to Verification of Considered Cause | طرق تعليل الأحكام عند الإمام ابن قيم الجوزية - Zuhrotul Ain Mansur (Al-Zahra : Journal for Islamic and Arabic Studies, 2009)
Verification of considered cause ( ta'lil al-ahkiim) together with the objectives of Shariah (maqiisid al-Shari'ah) is among the most important issues discussed by the experts of Jurisprudence. This article analyses the procedures of establishing causes for a certain law according to Ibnu Qayyim Al-Jauziyah,  a prominent salafi scholar who has written the subject in his book "I'liim al-muwiiqi'in " long time before Imam al-Syatibi who came up with theory of the objectives of Shariah. In his concept of ta'lil al-ahkiim, Al-J auziyah made a life interaction with texts of Islamic law resources through authentication of the texts, formulation of the causes and comparative studies on different  opinions  of  scholars on ta'lil and  tarjih.